Analyse of programming languages for numerical controlled measuring machines programming (part one) - Vasić, Siniša (Journal of Production Engineering, 1990)
Measuring machines made possible automatization of quality inspection in the metal working industry. Advantages of these metrological systems are speed of measuring performance, great accuracy andaccuracy of measuring results and subjective influence on the measuring results elimination as well. Besides of these, the computers added on measuring ma-chines, enable automatization of measuring results process-sing and analyze. Measuring machines application solve almost all of the metrological problems appear in practice: co-ordinate measurement and inspection, length measurement in the axis, in the plane and in the space, form and location inspection of characteristic geo-metrical shapes in the plane and in the space, form and location inspection of complex geometrical shapes in the plan and in the space (gears, crank-shafts, camshafts, turbine blades). Because of the effective realization of these metrological tasks, intensive software development for different generation of measuring machines is done. For CNC and DNC measuring machines several programming languages and systems.